(3QaY GdMLH GdeSJhQI aj eMGSf GdebUhQIs - (3ddTQja CHi GdbGSe eMeO Hf CMeOs; (3GHf MGRe GdbQWGLfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde HGdbde Chd GdbUjOI ddg eGbO gLJ jG jhe Gdfhi Ydi aDGOi ef HJGQjN GdLhi s
(3BNQgG (B:s
(3jfJgi HPcQ GdHjJ (B: (3hGdMeO ddg CLd ZGjI jHdZ HGdbhd dgG hjfJgi Hbhdg (B: (3hgPG BNQ TQM GdbUjOI hCbhd fjI GdeQA CHdZ ef GdYed ced s
(3GdfSNI HgG MhGTs
(3ef JMHjS CHj GdYHGS GdefUhQ HGddg Ydi LGeY GdbQhjjf HJGQjN YGe (B1303 (3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(854 / 40) s
Keywords: (3GdCOHs